The Interpretation of Plural Morphology and (Non-)Obligatory Number Marking: an Argument from Artificial Language Learning. Issue 4 (2nd October 2017) - Liter, Adam; Heffner, Christopher C.; Schmitt, Cristina
ABSTRACT: We present an artificial language experiment investigating (i) how speakers of languages such as English with two-way obligatory distinctions between singular and plural learn a system where singular and plural are only optionally marked, and (ii) how learners extend their knowledge of the plural morpheme when under the scope of negation without explicit training. Production and comprehension results suggest that speakers of English did learn a system with only optional marking of number. Additionally, subjects did not accept an inclusive ("one or more than one") interpretation of the plural when under the scope of negation, as in their native language, but rather assigned it an exclusive ("more than one") interpretation. The results are consistent with the hypothesis that the meaning assigned to plural morphology is sensitive to the architecture of the system. In a binary number system with obligatory number marking, plural morphology can sometimes receive an inclusive interpretation. However, in a system where plural marking is never obligatory, plural morphology has an exclusive interpretation.